Analysis of the influence of marl raw materials on the properties of portland cement - Duschanova Sanat K.; Boyjanov Islom R.; Kholmuratov Kholilla S.; Ismailov Erkinbay D.; Bekiev Murat A.; Ismoilov Rahmatjon I.; Akhmedov Munisbek M. (EPJ Web of Conferences)
This study presents a comprehensive analysis of the mineralogical composition of marl samples from the Meshkli mine using modern analytical methods. By employing combined X-ray diffraction and thermogravimetric analysis (TGA), complemented by high-resolution differential scanning calorimetry (DSC), we identified four distinct periods within the TG and DSC curves. Each of these periods is characterized by specific thermal effects, providing critical insights into the presence of hygroscopic water, combustion of organic compounds, oxidation of iron compounds, and thermal decomposition of calcite. Additionally, X-ray analyses reveal a variety of minerals, including calcite, quartz, montmorillonite, kaolinite, and hematite. These findings significantly enhance our understanding of the mineralogical aspects of the Meshkli mine marls. The purpose of this work is to investigate the physicochemical characteristics of Meshkli mine marl, which is novel for the silicate industry, and to assess its suitability for use in cement compositions. Macroscopically, the marl samples from the Meshkli mine exhibit a green color with yellow and brown spots. They consist of dense rock composed of finely dispersed calcite, clay minerals, and siltstone quartz grains. Chemical analysis indicates that Meshkli mine marl has a homogeneous chemical composition.